Barriers to Achieving Mathematics Proficiency: Synthesis of Research - Dictado, Maricris; Dagdag, Januard (Journal of Interdisciplinary Perspectives, 2025)
Mathematics education plays a crucial role in students’ academic development and real-world problem-solving. However, many high school students in the Philippines struggle to attain the expected learning competencies (ELCs)—defined as the grade-level mathematical skills and knowledge prescribed in the K to 12 curriculum. This literature review examines current research to identify and synthesize key factors contributing to the non-attainment of these competencies. Using a narrative review approach, the study analyzed peer-reviewed articles, policy reports, and local studies published from 2014 to 2024, focusing on challenges in secondary mathematics education. Twelve key factors were identified, including perceived irrelevance of mathematics to real-life, curriculum overload and fragmentation, time constraints, foundational gaps, ineffective teaching strategies, lack of classroom engagement, negative student attitudes, low student motivation, insufficient access to resources, misuse of technology, and ineffective assessment formats. These factors, both individually and collectively, hinder students' ability to achieve proficiency in mathematics. The review highlights the impact of these barriers on student learning. It suggests that addressing these challenges requires a comprehensive approach, including curriculum reforms, enhanced teacher training, and increased access to resources. Additionally, fostering a supportive learning environment that integrates real-world applications and utilizes clear, engaging teaching strategies can improve student motivation and achievement. This review emphasizes the need for continued research into these factors and their interactions to develop targeted interventions that can support students in overcoming the barriers to mathematics success.